2018
DOI: 10.1002/etep.2758
|View full text |Cite
|
Sign up to set email alerts
|

Grid power fluctuation reduction by fuzzy control based energy management system in residential microgrids

Abstract: Summary Smoothing grid profile plays a crucial role in dynamic operation of microgrid. This paper focuses on reducing the grid power fluctuation in a grid connected microgrid due to stochastic nature of renewable generations and its impact on the stability and quality of distribution network. To achieve this, the control strategies are designed to control the charging/discharging of battery storage system based on the difference between generations of renewable energy resources and load demand as well a batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Figure 8 shows the FL EPC performance, during the simulation, where the variation of P Bat , wich has numbers favorable for the SOC and remains within the limits of 50% and 100%. However this did not show a significant change, in addition, the peaks of power are −4kW and 2kW ; on the other hand, P Grid has peaks of power between −5kW and 5kW indicating a balance between the power injected and the power rectified [49], [50], [54].…”
Section: Numerical Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 8 shows the FL EPC performance, during the simulation, where the variation of P Bat , wich has numbers favorable for the SOC and remains within the limits of 50% and 100%. However this did not show a significant change, in addition, the peaks of power are −4kW and 2kW ; on the other hand, P Grid has peaks of power between −5kW and 5kW indicating a balance between the power injected and the power rectified [49], [50], [54].…”
Section: Numerical Resultsmentioning
confidence: 88%
“…Nowadays, three popular Fuzzy Logic strategies (FL) used as PMS are the Fuzzy Logic Control based on Net Power Trend (FLC NPT) [49], the Fuzzy Logic Control based on Energy Rate of Charge (FLC ERC) [50], and the Fuzzy Logic Control based on Grid Fluctuation (FLC GF) [54]. In the FLC NPT, the diffuse controller considers the tendency of the power flow in the MG to minimize the power exchange with the main grid; while extending the life of the storage unit against the charging and discharging cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A short‐term tie‐line fluctuation was analyzed in Reference 23, and a fuzzy logic controller was designed in a dynamic EMS to control the battery in a grid‐connected residential MG. However, the result showed that the method reduces tie‐line fluctuation but is unable to maintain constant tie‐line control.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a generic-based controller with flexible power flow capability has been proposed for hybrid microgrid in Eajal et al, 39 paying attention to the droop controllability of the distributed resources and bidirectional power flow in the interlinking converters. Several combined adaptive fault-tolerant control algorithms in Vargas-Martinez et al, 43 a hierarchical control included adaptive droop method and a new hybrid firefly optimized P-Q and V-f controller coordination in Satapathy et al 44 and a fuzzy control based on energy management system in Islam et al, 45 have been proposed to control various structures of a microgrid system. Designing the robustness, partial feedback linearization in Mahmud et al 41 and a feed-forward control strategy with internal model robust feedback control in Wang et al 42 has verified the importance of considering the nonlinearity features of microgrid dynamic models.…”
mentioning
confidence: 99%
“…Designing the robustness, partial feedback linearization in Mahmud et al 41 and a feed-forward control strategy with internal model robust feedback control in Wang et al 42 has verified the importance of considering the nonlinearity features of microgrid dynamic models. Several combined adaptive fault-tolerant control algorithms in Vargas-Martinez et al, 43 a hierarchical control included adaptive droop method and a new hybrid firefly optimized P-Q and V-f controller coordination in Satapathy et al 44 and a fuzzy control based on energy management system in Islam et al, 45 have been proposed to control various structures of a microgrid system.…”
mentioning
confidence: 99%